Force-Time Curve Variable Outcomes Following a Simulated Tennis Match in Junior Players. - Colomar, Joshua; Corbi, Francisco; Baiget, Ernest (Journal of Sports Science & Medicine, 2022)
This study examined the alterations induced by a simulated tennis competition on maximal isometric voluntary contraction (MVC), peak rate of force development (PRFD) and rate of force development (RFD) at different stages of contraction. Twenty junior tennis players performed an 80-minute simulated tennis match and two (pre and post) muscular performance tests. Variables tested included MVC, PRFD and RFD at 50, 100, 150 and 200 ms while performing a 90º shoulder internal rotation (IR90), 90º shoulder external rotation (ER90), shoulder horizontal adduction (ADD), shoulder horizontal abduction (ABD) and isometric midthigh pull (IMTP). Serve velocity (SV) was also registered. No significant changes were found regarding MVC, PRFD or SV. Non-significant moderate effect size (ES) towards a decrease in the IR90 RFD at 50 ms could be observed (16%; ES = 0.5) alongside an increase in the ADD and IMTP RFD at 150 ms (-15.8%, - 8.2%; ES = -0.53, -0.54) and IMTP RFD at 200 ms (-13%; ES = -0.54). Results indicate that MVC, PRFD, RFD at different time intervals and SV are unaltered following an 80-minute simulated match, possibly due to insufficient alterations triggered on key factors affecting the tested variables.